2020
DOI: 10.1099/ijsem.0.004018
|View full text |Cite
|
Sign up to set email alerts
|

Roseovarius arcticus sp. nov., a bacterium isolated from Arctic marine sediment

Abstract: An aerobic, Gram-stain-negative, motile, rod or long-rod-shaped bacterial isolate, strain MK6-18T, was isolated from a marine sediment sample from Kongsfjorden, Arctic. The bacterium grew optimally at 20 °C, pH 7.0 and in the presence of 1.0–2.0 % (w/v) NaCl. Phylogenetic analysis based on 16S rRNA gene sequences revealed that strain MK6-18T belonged to the genus Roseovarius . Its closest phylogenetic neighbour was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Members of the genus Roseovarius are catalase-positive, Gram-stain-negative, ovoid or rod-shaped, obligately aerobic bacteria. Most of Roseovarius type strains have been isolated from the marine environments such as coastal seawater [3], tidal flat [4], marine sediment [5], sponge [6] and whale bone [7]. By using high-throughput sequencing, a previous study found that the genus Roseovarius occurred in phytoplankton blooms and accounted for 0.15 % of the relative abundance of the bacterial community [8].…”
Section: Full-textmentioning
confidence: 99%
“…Members of the genus Roseovarius are catalase-positive, Gram-stain-negative, ovoid or rod-shaped, obligately aerobic bacteria. Most of Roseovarius type strains have been isolated from the marine environments such as coastal seawater [3], tidal flat [4], marine sediment [5], sponge [6] and whale bone [7]. By using high-throughput sequencing, a previous study found that the genus Roseovarius occurred in phytoplankton blooms and accounted for 0.15 % of the relative abundance of the bacterial community [8].…”
Section: Full-textmentioning
confidence: 99%
“…Roseovarius spp. are halophilic or halotolerant bacteria that thrive in various marine habitats ( 1 ). These bacteria have been reported as potential candidates for bioremediation and quorum sensing ( 2 , 3 ).…”
Section: Announcementmentioning
confidence: 99%
“…Catalase activity was tested through bubble production in 3 % ( For fatty acid analysis, strain HQ09 T and the reference strain CY03 T were grown on marine agar 2216 plates at 25°C for 36 h. Fatty acid methyl esters were analysed by a Hewlett Packard 6890 N gas chromatograph and identified using the Sherlock Microbial Identification System (version 6.2). Polar lipids of strains HQ09 T and CY03 T were extracted and analysed by two-dimensional thin-layer chromatography (silica gel plates, layer thickness 0.2 mm; Merck) as described previously [31,32]. Both strains were cultivated in marine broth 2216 for respiratory quinone analysis.…”
Section: Physiology and Chemotaxonomymentioning
confidence: 99%
“…Both strains were cultivated in marine broth 2216 for respiratory quinone analysis. Extraction and identification of respiratory quinones through HPLC (UltiMate 3000; Dionex) were performed as described previously [31].…”
Section: Physiology and Chemotaxonomymentioning
confidence: 99%